Impact of an online-guided physical activity intervention on cognition, resting-state brain connectivity, and the gut microbiome in healthy older adults—a randomized controlled trial - Simon J. Schrenk; Corinna Bang; Lena Best; Thomas Dost; Stefano Flor; Christiane Frahm; Christian Gaser; Rami Abou Hamdan; Marco Herbsleb; Christoph Kaleta; Fabian Kattlun; Hans-Josef Müller; et al. (GeroScience, 2026)
Introduction Physical activity may enhance cognition in older adults, yet evidence from randomized controlled trials (RCTs) on mechanistic pathways remains inconclusive. Methods This single-blinded RCT examined the effects of an 8-week, online-guided, multicomponent physical activity intervention on cognitive function, resting-state functional brain connectivity (rsFC), and the gut microbiome in 92 healthy older adults (M age = 66.35). Participants were randomized to a physical activity group performing moderate-to-vigorous-intensity aerobic, coordination, and balance exercises, or to an active control group engaging in progressive muscle relaxation and listening to aging-related podcasts. The primary outcome was change in visual processing speed (items/s) from pre- to post-assessment. Secondary outcomes included changes in additional cognitive measures, rsFC, cardiorespiratory fitness (CRF), and the gut microbiome. Results The primary outcome showed no significant between-group differences. However, exploratory analyses revealed potential improvements in inhibition ( η 2 = 0.061; p = 0.025) and visual memory ( η 2 = 0.047; p = 0.040) in the physical activity group. This group also showed a potential increase in rsFC between visual and dorsal attention networks ( η 2 = 0.101; p = 0.009). Visual memory gains correlated with improvements in rsFC ( p = 0.013). No between-group differences were observed in CRF or gut microbiome composition. Discussion While the primary outcome (visual processing speed) and predefined mechanistic pathways (e.g., gut microbiome composition) remained unaffected, this may partly reflect the sample’s high baseline fitness, which likely limited observable improvements. Exploratory findings suggest potential cognitive and associated rsFC benefits in memory and attention-related networks. The online format enabled a structured, scalable intervention while minimizing potential confounding from social interaction. Trial registration https://drks.de/search/de/trial/DRKS00028022 (date of registration: 14.02.2022).

Spatial variability of the coastal Wadden Sea fish community as revealed by environmental DNA - Suzanne SH. Poiesz; Johannes IJ. Witte; Judith DL. van Bleijswijk; Harry J. Witte; Evaline M. van Weerlee; Maartje Brouwer; Sanne Vreugdenhil; Henk W. van der Veer; Lise Klunder (Estuarine, Coastal and Shelf Science, 2025)

Stomach content analysis indicates multi decadal trophic stability in a temperate coastal fish food web, western Dutch Wadden Sea - Suzanne S.H. Poiesz; Johannes IJ. Witte; Henk W. van der Veer (Estuarine, Coastal and Shelf Science, 2024)

Historical trophic ecology of some divergent shark and skate species in the Dutch coastal North Sea zone - Suzanne S. H. Poiesz; Tomas van Elderen; Johannes IJ. Witte; Henk W. van der Veer (Marine Biology, 2021)

Association Between Systemic Inflammation, Carotid Arteriosclerosis, and Autonomic Dysfunction - Sven Rupprecht; S. Finn; D. Hoyer; A. Guenther; O. W. Witte; T. Schultze; M. Schwab (Translational Stroke Research, 2020)

Very Low Frequency Heart Rate Variability Predicts the Development of Post-Stroke Infections - Dirk Brämer; Albrecht Günther; Sven Rupprecht; Samuel Nowack; Josephine Adam; Fenja Meyer; Matthias Schwab; Ralf Surber; Otto W. Witte; Heike Hoyer; Dirk Hoyer (Translational Stroke Research, 2019)

Drivers of interannual variability in virioplankton abundance at the coastal western A ntarctic peninsula and the potential effects of climate change - Claire Evans; Joost Brandsma; David W. Pond; Hugh J. Venables; Michael P. Meredith; Harry J. Witte; Sharon Stammerjohn; William H. Wilson; Andrew Clarke; Corina P. D. Brussaard (Environmental Microbiology, 2017)
Summary An 8‐year time‐series in the Western Antarctic Peninsula (WAP) with an approximately weekly sampling frequency was used to elucidate changes in virioplankton abundance and their drivers in this climatically sensitive region. Virioplankton abundances at the coastal WAP show a pronounced seasonal cycle with interannual variability in the timing and magnitude of the summer maxima. Bacterioplankton abundance is the most influential driving factor of the virioplankton, and exhibit closely coupled dynamics. Sea ice cover and duration predetermine levels of phytoplankton stock and thus, influence virioplankton by dictating the substrates available to the bacterioplankton. However, variations in the composition of the phytoplankton community and particularly the prominence of Diatoms inferred from silicate drawdown, drive interannual differences in the magnitude of the virioplankton bloom; likely again mediated through changes in the bacterioplankton. Their findings suggest that future warming within the WAP will cause changes in sea ice that will influence viruses and their microbial hosts through changes in the timing, magnitude and composition of the phytoplankton bloom. Thus, the flow of matter and energy through the viral shunt may be decreased with consequences for the Antarctic food web and element cycling.

Phosphoinositide 3-Kinase γ Restrains Neurotoxic Effects of Microglia After Focal Brain Ischemia - Caroline Schmidt; Christiane Frahm; Nadine Schneble; Jörg P. Müller; Michael Brodhun; Irene Franco; Otto W. Witte; Emilio Hirsch; Reinhard Wetzker; Reinhard Bauer (Molecular Neurobiology, 2016)

Assessment of Interspecies Differences in Drug-Induced QTc Interval Prolongation in Cynomolgus Monkeys, Dogs and Humans - V. F. S. Dubois; W. E. A. de Witte; S. A. G. Visser; M. Danhof; O. Della Pasqua (Pharmaceutical Research, 2016)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Communication breakdown: clinicians disagree on subacromial impingement - Pieter Bas de Witte; Jurriaan H. de Groot; Erik W. van Zwet; Paula M. Ludewig; Jochem Nagels; Rob G. H. H. Nelissen; Jon P. Braman (Medical & Biological Engineering & Computing, 2014)

Cranial translation of the humeral head on radiographs in rotator cuff tear patients: the modified active abduction view - J. F. Henseler; P. B. de Witte; J. H. de Groot; E. W. van Zwet; R. G. H. H. Nelissen; J. Nagels (Medical & Biological Engineering & Computing, 2014)

Muscarinic receptor subtype mRNA expression in the human prostate: association with age, pathological diagnosis, prostate size, or potentially interfering medications? - Lambertus P. W. Witte; Christine A. Teitsma; Jean J. M. C. H. de la Rosette; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Climate Adaptation Services for the Netherlands: an operational approach to support spatial adaptation planning - H. Goosen; M. A. M. de Groot-Reichwein; L. Masselink; A. Koekoek; R. Swart; J. Bessembinder; J. M. P. Witte; L. Stuyt; G. Blom-Zandstra; W. Immerzeel (Regional Environmental Change, 2013)

Synthesis of ecosystem vulnerability to climate change in the Netherlands shows the need to consider environmental fluctuations in adaptation measures - P. M. van Bodegom; J. Verboom; J. P. M. Witte; C. C. Vos; R. P. Bartholomeus; W. Geertsema; A. Cormont; M. van der Veen; R. Aerts (Regional Environmental Change, 2013)

The relationship between impulsivity and craving in alcohol dependent patients - L. Joos; A. E. Goudriaan; L. Schmaal; N. A. J. De Witte; W. Van den Brink; B. G. C. Sabbe; G. Dom (Psychopharmacology, 2013)

Erratum to: MG624, an α7-nAChR antagonist, inhibits angiogenesis via the Egr-1/FGF2 pathway - Kathleen C. Brown; Jamie K. Lau; Aaron M. Dom; Theodore R. Witte; Haitao Luo; Clayton M. Crabtree; Yashoni H. Shah; Brandon S. Shiflett; Aileen J. Marcelo; Nancy A. Proper; W. Elaine Hardman; Richard D. Egleton; et al. (Angiogenesis, 2012)

MG624, an α7-nAChR antagonist, inhibits angiogenesis via the Egr-1/FGF2 pathway - Kathleen C. Brown; Jamie K. Lau; Aaron M. Dom; Theodore R. Witte; Haitao Luo; Clayton M. Crabtree; Yashoni H. Shah; Brandon S. Shiflett; Aileen J. Marcelo; Nancy A. Proper; W. Elaine Hardman; Richard D. Egleton; et al. (Angiogenesis, 2012)

Muscarinic receptor subtypes and signalling involved in the attenuation of isoprenaline-induced rat urinary bladder relaxation - Lambertus P. W. Witte; Noach de Haas; Mathai Mammen; Eric L. Stangeland; Tod Steinfeld; Jayashree Aiyar; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Recognition of Clostridium difficile PCR-ribotypes 001, 027 and 126/078 using an extended MALDI-TOF MS system - M. Reil; M. Erhard; E. J. Kuijper; M. Kist; H. Zaiss; W. Witte; H. Gruber; S. Borgmann (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Prevalence and molecular characteristics of methicillin-resistant Staphylococcus aureus (MRSA) among pigs on German farms and import of livestock-related MRSA into hospitals - R. Köck; J. Harlizius; N. Bressan; R. Laerberg; L. H. Wieler; W. Witte; R. H. Deurenberg; A. Voss; K. Becker; A. W. Friedrich (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Habitat related growth and reproductive investment in estuarine waters, illustrated for the tellinid bivalve Macoma balthica (L.) in the western Dutch Wadden Sea - Joana F. M. F. Cardoso; Johannes IJ. Witte; Henk W. van der Veer (Marine Biology, 2007)

Viruses as mortality agents of picophytoplankton in the deep chlorophyll maximum layer during IRONAGES III - Anne-Claire Baudoux; Marcel J. W. Veldhuis; Harry J. Witte; Corina P. D. Brussaard (Limnology and Oceanography, 2007)
We report viral‐induced mortality rates of the picoeukaryotic (two size classes) and prokaryotic (cyanobacteria Prochlorococcus and Synechococcus ) phytoplankton during a cruise in the oligotrophic subtropical northeastern Atlantic (October 2002). A dilution assay, simultaneously estimating viral lysis and microzooplankton grazing, was applied around the deep chlorophyll maximum (DCM) at six stations. For the smallest picoeukaryotes (group I), viral lysis was responsible for 50‐100% of the total cell losses, with rates ranging from 0.1 to 0.8 d −1 . Viral lysis rates were positively linked to the abundance and contribution of large genome‐sized (180–225 kb) putative algal viruses. In contrast, the prokaryotic picophytoplankton did not seem to be controlled by viral lysis. For Synechococcus , microzooplankton grazing dominated, with rates between 0.1 and 0.25 d −1 (comparable to those for the eukaryotic algae). For Prochlorococcus , both viral lysis and microzooplankton grazing rates were very low (0–0.1 d −1 ). Overall, the total carbon production by the picophytoplankton community was balanced by the combined losses due to viral lysis and microzooplankton grazing. Viral lysis released 0.1‐0.3 µg of picophytoplanktonic C L −1 d −1 , which comprised 21% of the total carbon production by picophytoplankton.

Abnormal recruitment of periendothelial cells to lymphatic capillaries in digestive organs of angiopoietin-2-deficient mice - Hiroshi Shimoda; Michael J. Bernas; Marlys H. Witte; Nicholas W. Gale; George D. Yancopoulos; Seiji Kato (Cell and Tissue Research, 2007)

Spatial and seasonal patterns in the feeding habits of juvenile Lates niloticus (L.), in the Mwanza Gulf of Lake Victoria - E. F. B. Katunzi; W. L. T. Van Densen; J. H. Wanink; F. Witte (Hydrobiologia, 2006)

Variants in Deleted in AZoospermia-Like (DAZL) are correlated with reproductive parameters in men and women - Joyce Y. Tung; Mitchell P. Rosen; Lawrence M. Nelson; Paul J. Turek; John S. Witte; Daniel W. Cramer; Marcelle I. Cedars; Renee A. Reijo Pera (Human Genetics, 2006)

Characterization of methicillin-resistant Staphylococcus aureus from Ulaanbaatar, Mongolia - D. Orth; K. Grif; L. Erdenechimeg; C. Battogtokh; T. Hosbayar; B. Strommenger; C. Cuny; G. Walder; C. Lass-Flörl; M.P. Dierich; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Spread of ampicillin/vancomycin-resistant Enterococcus faecium of the epidemic-virulent clonal complex-17 carrying the genes esp and hyl in German hospitals - I. Klare; C. Konstabel; S. Mueller-Bertling; G. Werner; B. Strommenger; C. Kettlitz; S. Borgmann; B. Schulte; D. Jonas; A. Serr; A. M. Fahr; U. Eigner; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

New strains of community-acquired methicillin-resistant Staphylococcus aureus with Panton–Valentine leukocidin causing an outbreak of severe soft tissue infection in a football team - M. Müller-Premru; B. Strommenger; N. Alikadic; W. Witte; A. W. Friedrich; K. Seme; N. Svent Kucina; D. Smrke; V. Spik; M. Gubina (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Panton–Valentine leukocidin-positive methicillin-resistant Staphylococcus aureus in Germany associated with travel or foreign family origin - J. Maier; H. Melzl; U. Reischl; I. Drubel; W. Witte; N. Lehn; H. Linde (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Healthcare-associated outbreaks and community-acquired infections due to MRSA carrying the Panton-Valentine leucocidin gene in southeastern Germany - H. Linde; F. Wagenlehner; B. Strommenger; I. Drubel; J. Tanzer; U. Reischl; U. Raab; C. Höller; K. G. Naber; W. Witte; F. Hanses; B. Salzberger; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Use of novel, non-imidazole inverse agonist radioligands to define histamine H3 receptor pharmacology - T. A. Esbenshade; B. B. Yao; D. G. Witte; T. L. Carr; R. Sharma; J. L. Baranowski; K. M. Krueger; T. R. Miller; B. W. Surber; R. Faghih; A. A. Hancock (Inflammation Research, 2005)

Emergence of methicillin-resistant Staphylococcus aureus with Panton?Valentine leukocidin genes in central Europe - W. Witte; C. Braulke; C. Cuny; B. Strommenger; G. Werner; D. Heuck; U. Jappe; C. Wendt; H.-J. Linde; D. Harmsen (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Use-dependent cortical plasticity in thalidomide-induced upper extremity dysplasia: evidence from somaesthesia and neuroimaging - M. C. Stoeckel; B. Pollok; A. Schnitzler; O. W. Witte; R. J. Seitz (Experimental Brain Research, 2004)

Localization of the Na + -d-glucose cotransporter SGLT1 in the blood-brain barrier - Katrin Elfeber; Alwin Khler; Michael Lutzenburg; Christina Osswald; Hans-Joachim Galla; Otto W. Witte; Hermann Koepsell (Histochemistry and Cell Biology, 2004)

Obvious Lack of Association Between Dynamics of Epidemic Methicillin-Resistant Staphylococcus aureus in Central Europe and agr Specificity Groups - G. Werner; W. Witte; B. Strommenger; C. Cuny (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Risk Factors for Nasal Carriage of Staphylococcus aureus in Infectious Disease Patients, Including Patients Infected with HIV, and Molecular Typing of Colonizing Strains - D. Sissolak; A. Geusau; G. Heinze; W. Witte; M. Rotter (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Evaluation of a Reverse Hybridization Blot Test for Detection of Oxacillin-Resistant Staphylococcus aureus - C. Cuny; S. Salmenlinna; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Clinical and Genetic Analysis of Staphylococcus aureus Nasal Colonisation and Exit-Site Infection in Patients Undergoing Peritoneal Dialysis - B. Kreft; S. Eckstein; A. Kahl; U. Frei; W. Witte; M. Trautmann (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Selective Sequestration of Pyrrolizidine Alkaloids from Diverse Host Plants by Longitarsus Flea Beetles - S. Dobler; W. Haberer; L. Witte; T. Hartmann (Journal of Chemical Ecology, 2000)

Detection of Oxacillin Resistance in Staphylococcus aureus by Screening Tests - C. Cuny; B. Pasemann; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Methicillin-Resistant Staphylococcus aureus Exhibiting Genomic Fingerprints of Phage Group I Strains in a Hospital and in a Nurse's Family - C. Windmeier; C. Cuny; C. Braulke; D. Heuck; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

A novel type of adhering junction in an epithelioid tumorigenic rat cell culture line - M. Schmelz; Dennis L. Way; Peter Borgs; Wiebke K. Peitsch; Hannelore Schmidt; Marlys H. Witte; Charles L. Witte; W. W. Franke; R. Moll (Cell and Tissue Research, 1998)

Association between Quinupristin/Dalfopristin Resistance in Glycopeptide-Resistant Enterococcus faecium and the Use of Additives in Animal Feed - G. Werner; I. Klare; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Measured and modelled water transport in the Odra Estuary for the flood period July/August 1997 - W. Rosenthal; T. Wolf; G. Witte; W. Buchholz; P. Rybaczok (Ocean Dynamics, 1998)

Association between quinupristin/dalfopristin resistance in glycopeptide-resistantEnterococcus faecium and the use of additives in animal feed - G. Werner; I. Klare; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Influenza A Outbreak among Adolescents in a Ski Hostel - O. Lyytikäinen; E. Hoffmann; H. Timm; B. Schweiger; W. Witte; U. Vieth; A. Ammon; L. R. Petersen (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Use of the multi-allelic self-incompatibility gene in apple to assess homozygocity in shoots obtained through haploid induction - L. Verdoodt; A. Van Haute; I. J. Goderis; K. De Witte; J. Keulemans; W. Broothaerts (Theoretical and Applied Genetics, 1998)

Influenza a outbreak among adolescents in a ski hostel - O. Lyytikäinen; E. Hoffmann; H. Timm; B. Schweiger; W. Witte; U. Vieth; A. Ammon; L. R. Petersen (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Meat preparation and colorectal adenomas in a large sigmoidoscopy-based case-control study in California (United States) - Nicole M. Probst-Hensch; Rashmi Sinha; Matthew P. Longnecker; John S. Witte; Sue A. Ingles; Harold D. Frankl; Eric R. Lee; Robert W. Haile (Cancer Causes & Control, 1997)

Dynamics of PhiX174 protein E-mediated lysis of Escherichia coli - A. Witte; G. Wanner; M. Sulzner; W. Lubitz (Archives of Microbiology, 1992)

Correlation of the colony-forming abilities of xeroderma pigmentosum fibroblasts with repair-specific DNA incision reactions catalyzed by cell-free extracts - H. W. Thielmann; I. Witte (Archives of Toxicology, 1980)